1997
DOI: 10.1046/j.1464-410x.1997.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sildenafil, a type‐5 cGMP phosphodiesterase inhibitor, and papaverine on cyclic GMP and cyclic AMP levels in the rabbit corpus cavernosum in vitro

Abstract: Objective  To investigate further the mechanisms of action of sildenafil, a highly selective and potent inhibitor of type 5 cGMP phosphodiesterase (PDE5) that has proved effective in the treatment of erectile dysfunction, by assessing its effect on the in vitro formation of cGMP and cAMP in the corpus cavernosum of the rabbit. Materials and methods  Male New Zealand White rabbits (2.5 kg) were killed and their penises rapidly excised, cut into segments and pooled. Penile segments were then incubated with vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(118 citation statements)
references
References 3 publications
(8 reference statements)
6
109
0
3
Order By: Relevance
“…It is a nonspecific phosphodiesterase (PDE) inhibitor that increases cyclic AMP and cyclic GMP. 78 Phentolamine, another vasoactive agent, is a direct a-adrenoceptor blocker. However, phentolamine alone cannot produce rigid erections, so it is commonly used in combination with other agents.…”
Section: Ic Injections Ic Injections Were First Introduced In Early 1mentioning
confidence: 99%
“…It is a nonspecific phosphodiesterase (PDE) inhibitor that increases cyclic AMP and cyclic GMP. 78 Phentolamine, another vasoactive agent, is a direct a-adrenoceptor blocker. However, phentolamine alone cannot produce rigid erections, so it is commonly used in combination with other agents.…”
Section: Ic Injections Ic Injections Were First Introduced In Early 1mentioning
confidence: 99%
“…Therefore, the combination of sildena®l plus intraurethral or intracavernosal PGE 1 , or intracavernosal forskolin or VIP, might be effective in patients with ED in whom monotherapy with these agents has failed. That papaverine and sildena®l were not synergistic in this study might be because they have similar mechanisms of action on the relaxation of cavernosal smooth muscles [20,26,27]. To ascertain why there are different synergistic effects of cAMP-mediated agents plus sildena®l, the intracellular cAMP level should be measured, and expression and functional studies of receptors of VIP and PGE 1 after treatment with forskolin, VIP and PGE 1 conducted in cavernosal smooth muscles.…”
Section: Discussionmentioning
confidence: 94%
“…Doherty et al [19] reported that direct injection of various PGE 5 inhibitors into cat corpus cavernosum caused dose-dependent increases in intracorporal pressure. Furthermore, Jeremy et al [20] reported that 10 mmol/L sildena®l alone increased the cGMP level up to ®ve-fold in rabbit corpus cavernosum tissue, and up to 28-fold in the presence of 1 mmol/L SNP. Reportedly, sildena®l alone signi®cantly reduced the basal tone in unstimulated rabbit cavernosal smooth muscle [18].…”
Section: Discussionmentioning
confidence: 99%
“…20 It has a very de®nite effect upon erectile activity in humans 21 and sildena®l promotes penile erection through increased intracellular cGMP in response to sexual stimulation potentiating smooth muscle relaxation. 22 In this study, papaverine was used as a standard inhibitor, and all results obtained with other more speci®c inhibitors were compared with papaverine. Zaprinast and sulmazole, cGMP-speci®c PDE inhibitors, 23 relaxed corpus cavernosum with pD 2 Figure 2 (a) Zaprinast concentration ± response curves in isolated rabbit corpus cavernosum strips precontracted with phenylephrine 10 76 ± 3610 76 M. Each point is expressed as a percentage of the contraction induced by phenylephrine and is given as the mean AE s.e.m.…”
Section: Effects Of the Speci®c Phosphodiesterase Inhibitors T Utkan mentioning
confidence: 99%